Obat Herbal Berbasis Bukti Untuk Hepaprotektor - Dewi Agustini, Ni Putu; Anita Dewi, Ni Luh Kade Arman; Megawati, Fitria; Wulandari, Ratna (Usadha, 2022)
Liver damage can occur due to infection, viruses, drug use, and the environment. Paracetamol is a drug that has analgesic and antipyretic effects, but on the other hand the use of paracetamol in excessive doses (15/day) can cause liver damage. This can occur because the process of paracetamol metabolism in the liver forms a reactive metabolite known as N-acetyl-pbenzoquinonemine (NAPQI). The hepatoprotective mechanism can be seen from the ability of Ichnocarpus frutescens to ward off free radicals formed from the process of lipid oxidation due to the reactive metabolite of paracetamol, namely NAPQI. The method used is a literature review which is a systematic, explicit and reproducible method for carrying out identification, evaluation and synthesis of research works and ideas that have been produced by researchers and practitioners. The data base used is National and International Journal Websites such as Google Scholar.